Pengendalian Kualitas Produk Cacat PHX Toshiba Pada PT Schneider Electric Manufacturing Batam - Singgih Wardana; Nofriani Fajrah (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2019)
Abstract— Quality in the modern world is very influential in developing and advancing a company. PT. Schneider Electric Manufacturing Batam is a manufacturing company electrical systems. In terms of time, the resulting waste is in the form of product delays that will be sent to the shipping because the product to be sent to shipping must be full in one pallet. If there is a defective product, it must wait for the defective product to be analyzed and repaired. This study aims to analyze phx toshiba product control and to identify the causes of phx toshiba product defects with the Statistical Process Control method in the form of a p chart. Based on the results of the control chart, the proportion of product defects for PHX Toshiba VFS15 is still within the control limit because none of the data exits the control limit of 3 sigma or 4 sigma. There are several factors that cause the occurrence of broken defective products that are analyzed using a causal diagram, namely human factors (operators), machine factors (setting parameters and voltage unstable), method factors (methods of installing product testing tools and operating methods), material factors (not good material) and environmental factors (soldering fumes).